El teletrabajo y su relación con el tecnoestrés laboral post COVID-19 - Alvitez Sifuentes, Cristian Giancarlo (2024)
The overwhelming use of information and communications technologies (ICT) that is being implemented in organizations makes it necessary to analyze the effects of teleworking on employees. The objective of this review was to analyze the scientific literature published on the relationship between teleworking and work-related technostress in the post-COVID-19 context. The method used had a qualitative approach, carrying out a systematic review that respected the PRISMA guidelines. 20 empirical investigations found in Scopus and Google Scholar were analyzed, published between 2019 and 2023. The results categorically indicate that there is a close relationship between teleworking and work-related technostress. The factors are social isolation, complex software, conflict between work and the personal environment, the absence of interpersonal relationships, and technological uncertainty. Therefore, it is suggested that organizations promote work autonomy and effective self-leadership, in addition to considering measures such as training in the use of digital platforms, the implementation of high-quality software that allows better interaction, and the organization of periodic face-to-face activities.